Rethinking Politeness Principle in Pragmatics Study - Alfin Rosyidha; Irfi N. Afdiyani; Ayu D. Fatimah; Izzatun Nisa (State institute of islamic studies salatiga, 2019)
The study focuses on Politeness Principle found in the movie Kung Fu Panda 1 using Leech’s theory.Leech defines politeness as forms of behaviour that establish and maintain comity. He proposed six types of politeness maxim such as tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. The objectives of this study are to classify the type of politeness maxim used in the movie, to know the frequency of the most and the least maxim used in the movie, and to explain how the figures in the movie used politeness principle in the communication.The writers used descriptive analysis in analyzing the politeness principle used in the movie and used a simple quantitative analysis to know the frequency of the politeness principle. The result of the study shows that all politeness maxim is used in the movie with the frequency tact maxim 10 utterances (9,8%), generosity maxim 5 utterances (4,9%), approbation maxim 24 utterances (23,5%), modesty maxim 11 utterances (10,8%), agreement maxim 45 utterances (44,1%), and sympathy maxim 7 utterances (6,9%).Keywords: Pragmatics, Politeness principle, Movie.